Molecular characterization of the SUMO-1 modification of RanGAP1 and its role in nuclear envelope association - Mahajan, Rohit; Gerace, Larry; Melchior, Frauke (The journal of cell biology, 1998)
The mammalian guanosine triphosphate (GTP)ase-activating protein RanGAP1 is the first example of a protein covalently linked to the ubiquitin-related protein SUMO-1. Here we used peptide mapping, mass spectroscopy analysis, and mutagenesis to identify the nature of the link between RanGAP1 and SUMO-1. SUMO-1 is linked to RanGAP1 via glycine 97, indicating that the last 4 amino acids of this 101- amino acid protein are proteolytically removed before its attachment to RanGAP1. Recombinant SUMO-1 lacking the last four amino acids is efficiently used for modification of RanGAP1 in vitro and of multiple unknown proteins in vivo. In contrast to most ubiquitinated proteins, only a single lysine residue (K526) in RanGAP1 can serve as the acceptor site for modification by SUMO-1. Modification of RanGAP1 with SUMO-1 leads to association of RanGAP1 with the nuclear envelope (NE), where it was previously shown to be required for nuclear protein import. Sufficient information for modification and targeting resides in a 25-kD domain of RanGAP1. RanGAP1-SUMO-1 remains stably associated with the NE during many cycles of in vitro import. This indicates that removal of RanGAP1 from the NE is not a required element of nuclear protein import and suggests that the reversible modification of RanGAP1 may have a regulatory role.